CONTRIBUTION TO THE RECOGNITION OF THE STRUCTURE OF TASSAOUT DOWNSTREAM OF TADLA BASIN THROUGH THE APPLICATION OF GEOELECTRIC METHODS - Khoulaid F.; Bahi L.; Najine A.; Wafik A. (European Scientific Journal, ESJ, 2015)
Geoelectric study is used in determining the image of the structure of the aquiferous system of the Tadla plain (Tessaout aval) through the measure of electric soundings. The treatment processing of these measures, their correlation with the data of certain drilling, the well existing in the canvassed area, and the analysis of all the results, shows that the study area of the profiles and the maps of the established electrics resistivities and clear geoelectric cups gives a general looks. This put the superimposing of several variables as evidence. Roughly speaking, grounds draws a structure of monoclonal wrinkle sometimes tectonised, which dives the Northwest towards the Southeast. This structure is affected by a series of flaws which are causing the collapse of compartments which are located in the South.